Acute heart failure related to a large left atrial myxoma. Issue 3 (3rd July 2018) - Chiariello, Giovanni A.; Bruno, Piergiorgio; Colizzi, Christian; Pavone, Natalia; Nesta, Marialisa; Cammertoni, Federico; Mazza, Andrea; Posteraro, Alfredo; Perri, Gianluigi; Massetti, Massimo
ABSTRACT: An association between atrial myxoma and left ventricular failure is rarely described, is not completely understood, and may have multiple etiologies. We present a 49-year-old man with no history of cardiovascular disease who was admitted to our hospital with pulmonary edema. He was in atrial fibrillation with rapid ventricular response. Echocardiography showed a 10.5-cm left atrial myxoma, which had been asymptomatic until the onset of congestive heart failure in the presence of severe left ventricular systolic dysfunction. Left ventricular inflow obstruction associated with the giant atrial mass could not be the only cause for acute heart failure.